2010
DOI: 10.1073/pnas.1009396107
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin selectively influences moral judgment and behavior through effects on harm aversion

Abstract: Aversive emotional reactions to real or imagined social harms infuse moral judgment and motivate prosocial behavior. Here, we show that the neurotransmitter serotonin directly alters both moral judgment and behavior through increasing subjects' aversion to personally harming others. We enhanced serotonin in healthy volunteers with citalopram (a selective serotonin reuptake inhibitor) and contrasted its effects with both a pharmacological control treatment and a placebo on tests of moral judgment and behavior. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
307
3
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 432 publications
(344 citation statements)
references
References 65 publications
(101 reference statements)
23
307
3
11
Order By: Relevance
“…In addition, abnormal lack of empathy and amoral conduct of individuals with antisocial personality disorders impose considerable distress on their social environment, underscoring the need for effective pharmacological treatments to complement existing cognitive-behavioral approaches. Consistent with the observations of prior studies (10), the work by Crockett et al (4) suggests that serotonin augmentation might be a promising strategy to increase the emotional response of the amygdala and associated structures in individuals with social dysfunction. As illustrated by the emerging clinical success story of oxytocin (18,19), the strategy to translate pharmacological results guided by social neuroscience to clinical therapy holds considerable promise.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…In addition, abnormal lack of empathy and amoral conduct of individuals with antisocial personality disorders impose considerable distress on their social environment, underscoring the need for effective pharmacological treatments to complement existing cognitive-behavioral approaches. Consistent with the observations of prior studies (10), the work by Crockett et al (4) suggests that serotonin augmentation might be a promising strategy to increase the emotional response of the amygdala and associated structures in individuals with social dysfunction. As illustrated by the emerging clinical success story of oxytocin (18,19), the strategy to translate pharmacological results guided by social neuroscience to clinical therapy holds considerable promise.…”
supporting
confidence: 78%
“…This is consistent with the interpretation that increased serotonin made subjects more likely to tolerate behavior that violates an ethical imperative (fairness) because punishing it would have (financially) harmed fellow coplayers. With these convergent observations, the study by Crockett et al (4) demonstrates that enhanced serotonin biases moral judgment and decision making toward sociality.…”
mentioning
confidence: 98%
“…Specifically, impaired fear decoding emerged as the main predictor of utilitarian choices for high-conflict dilemmas, whereas impaired disgust decoding emerged as the main predictor of utilitarian choices for low-conflict dilemmas. Although future work is required to explore these effects, we suggest that the perception of fear in specific individuals may lead to an aversion to harming those individuals even when doing so may lead to saving other people, as in high-conflict scenarios (Crockett et al, 2010). On the other hand, low-conflict scenarios (e.g., causing harm for selfish benefit) may trigger moral disgust (Ugazio et al, 2012;Wheatley and Haidt, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serotonin dysfunction affects social cognition and behavior; for instance, animal research has shown that serotonin suppresses reactive aggression and promotes affiliate actions linked to social status in primates (Dayan and Huys, 2009). Moreover, human research has shown that tryptophan depletion (that decreases 5-HT availability) reduces cooperative behavior in a prisoner's dilemma game (Wood et al, 2006), whereas citalopram administration made subjects more likely to judge harmful actions as forbidden (Crockett et al, 2010) and enhanced reward sensitivity to facial expressions of a social partner (Tse et al, 2014). FMRI studies have found that citalopram reduces negative self-referential processing in depressed patients by enhancing medial PFC activity (Di Simplicio et al, 2012), and normalizes resting-state connectivity with the dorsal medial PFC (McCabe et al, 2011).…”
Section: Escitalopram Effects In Iedmentioning
confidence: 99%